IMPLEMENTASI TEKNOLOGI DIGITAL DALAM TRANSFORMASI PERPUSTAKAAN UNIVERSITAS HASANUDDIN - Ahmad Dhani R; Ismaya; Muhammad Nasrul; Syahdan; Zainal Potton (STKIP Subang, 2026)
This study aims to describe the implementation of digital technology in the transformation of Hasanuddin University Library, analyze the readiness of infrastructure and human resources, and identify the factors influencing users’ utilization of digital library services. This research employed a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation involving library managers, librarians, and users as informants. The findings indicate that Hasanuddin University Library has implemented various digital services, including Online Public Access Catalog (OPAC), institutional repository, e-journal access, collection search services, and several system-based administrative services. These digital services provide users with faster, more flexible, and more efficient access to information. In terms of internal management, processes such as bibliographic data entry, metadata processing, collection inventory, and collection data storage have also begun to shift toward digital systems. The readiness of infrastructure, human resources, and supporting systems is generally adequate, as indicated by the availability of internet networks, computer devices, servers, and library automation systems. However, several obstacles remain, including network disruptions, system stability issues, data security concerns, limited integration among platforms, budget constraints, and metadata quality that has not yet been fully standardized. The utilization of digital library services is influenced by ease of access, time efficiency, content relevance, service quality, and users’ academic needs. Overall, the digital transformation of Hasanuddin University Library has had a positive impact on library services, although continuous development is still required to ensure that digital services operate more optimally.